2011
DOI: 10.1016/j.ijsu.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the natural course of compensatory sweating following thoracoscopic sympathectomy

Abstract: Thoracoscopic sympathectomy is effective in the treatment of hyperhydrosis. However compensatory sweating seems unavoidable and infrequently improves with time. Patients need to be carefully counselled before committing to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Previous studies have reported that thoracoscopic sympathectomy cures or reduces essential hyperhydrosis with a success rate and satisfaction over 90 % (2, 6, 8, 9). Some articles have reported that the degree of satisfaction after surgery decreases with time and type of hyperhidrosis (palmar, axillary, plantar), while there is controversy about the role of limiting sympathectomy on the degree of satisfaction (6, 10-12).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that thoracoscopic sympathectomy cures or reduces essential hyperhydrosis with a success rate and satisfaction over 90 % (2, 6, 8, 9). Some articles have reported that the degree of satisfaction after surgery decreases with time and type of hyperhidrosis (palmar, axillary, plantar), while there is controversy about the role of limiting sympathectomy on the degree of satisfaction (6, 10-12).…”
Section: Discussionmentioning
confidence: 99%
“…Because all patients presented with great improvement at the sites of primary hyperhidrosis after operation (and maintained this improvement at enrollment; these patients stated that there was no sweating at the primary sites), it is very likely that the poor QOL is attributable to CH. Unfortunately, preliminary data seem to indicate that spontaneous long-term amelioration does not occur [23].…”
Section: Commentmentioning
confidence: 99%
“…Though the theories behind the origin of this phenomenon are still unclear [1], the existence of this side effect of sympathectomy is considered one of the most important limitations of the surgical treatment of primary hyperhidrosis and facial blushing, and it does not seem to diminish with time [2, 3]. The pathogenetic concepts behind the compensatory sweating (CH) have been presented in the Guidelines of Brazilian Thoracic Surgery Society (BTSS) in 2008 [1].…”
Section: Introductionmentioning
confidence: 99%